Change in ocular refraction after tropicamide cycloplegia in preschool children - Nawrot, Paweł; Przekoracka-Krawczyk, Anna; Perz, Katarzyna; Rusiak, Patrycja; Naskręcki, Ryszard (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: The aim of the study was to evaluate changes in ocular refraction after 1% tropicamide and its efficacy in diagnosing refractive errors in preschool children. Material and methods: 116 children (232 eyes) at the age of 5 to 6 years participated in the study. An objective examination of refraction using autorefractor before and after 1% tropicamide cycloplegia (2 x 1 drop of the agent instilled 5 min apart) was performed in the study. Results: After the instillation of tropicamide, the spherical component of the refractive error significantly increased by +0.78 D, while the cylindrical component (i.e. its power and axis) remained unaltered. In examining the refractive error, the mean value of the spherical component in children at the age of 5 to 6 years amounted to +1.55 D, in the cylindrical component mean value was -0.51 D, and the axis was 102°. Conclusions: 1% Tropicamide appears an effective cycloplegic agent in preschool children, excluding children with high hyperopia, anisometropia, or strabismus.